Characterization of the physical properties and sensory acceptability of Caulerpa racemosa grain beverage. Issue 1 (November 2021) - Sinurat, E; Nurhayati,; Fransiska, D; Basmal, J
Abstract: Caulerpa racemosa grain was a healthy product and high nutrition. This study applied study was applied Caulerpa racemosa grain in the beverage with the addition of alginate powder. Thus, the present work was aimed to determine the properties of beverage C . racemosa grain formulated with the alginate concentration was varied (0; 0.025; 0.05; 0.075; 0.10 and 0.125 %). The testing of quality beverage C . racemosa viscosity was analyzed using viscometer methods. The colorimeter investigated the colour. The sensory acceptability hedonic and score method (colour, appearance, aroma, taste, texture, and overall acceptance) used a 5-point. Results showed that alginate used alginate 0.025%, the highest preference, aroma, and appearance scores. The addition of alginate increased alginate was increased the viscosity of beverage C. racemosa grain. The colour of C. racemosa grain progressively became light as the level of alginate grew. However, the increased alginate is not significant enough to change the redness and greenness value of C. racemosa grain beverage. The panelists have preferred to drink the selected Caulerpa grain beverage (concentration sodium alginate 0.025%), with slightly viscous.